Key concepts in world philosophies : everything you need to know about doing. (London [England] : Bloomsbury, 2022)
"Crossing continents and traveling through the centuries, Key Concepts in World Philosophies brings together over 30 of the core ideas associated with the major Indian, Chinese, Japanese, Islamic, African, Ancient Greek and modern European philosophers. What connects these foundational ideas is the universal theme of transformation: how has each concept sought to change our way of understanding the world we live in or the life we are living? From Socratic logos and Chinese xin to reason in 18th-century Germany and equity in Islamic thought, an international team of experts cover a diverse set of ideas and theories originating from thinkers such as Kant, Confucius, Buddha, Dogen, Nietzsche, Zhuangzi, Hegel and Husserl. Divided into three sections organised around the major themes of knowledge, metaphysics, and aesthetics, each short chapter provides an introductory overview with contextual background, supported by discussion questions and further reading suggestions. Beginning with an introduction that explains how these concepts can be used as tools in contexts outside of their own, this one-of-a-kind study guide allows you to read philosophical texts from all over the world, understand how to practice cross-cultural philosophy and find out how philosophical ideas can be applied to your own life."--
How to Use This Book Introduction: How Philosophy Can Transform Our Lives -- Philosophy as a Way of Life, Sarah Flavel (Bath Spa University and International Academy for Chinese Thought and Culture , UK) and Chiara Robbiano (University College Utrecht, the Netherlands and Tohoku University, Japan) Part I: How we Acquire Knowledge Introduction, Sarah Flavel (Bath Spa University and International Academy for Chinese Thought and Culture , UK) and Chiara Robbiano (University College Utrecht, the Netherlands and Tohoku University, Japan) 1. Ancient and Classical Meanings of the Terms wu and wei in Chinese Philosophy, Douglas L. Berger (Leiden University, the Netherlands) and Yuan Zhang (Heifei Normal University, China) 2. 'Knowing' (zhi) in Early Chinese Philosophy, Aaron B Creller (University of North Florida, USA) 3. Dogen's Concept of 'shinjin gakudou' in Buddhist and East Asian Thought, Bret W. Davis (Loyola University Maryland, USA) 4. 'Heart-Mind' ( xin ), in Chinese Philosophy, Dascha Düring (Utrecht University, the Netherlands) 5. 'Radical Perspectivism' in Nietzsche and the Zhuangzi, Sarah Flavel (Bath Spa University, UK) 6. Scepticism and the 'Prasanga' Method in Classical Indian Thought, Ethan Mills (University of Tennessee at Chattanooga, USA) 7. Reason, Socratic logos and Kantian Vernunft in Western Philosophy, Johannes, M. van Ophuijsen (Utrecht University, the Netherlands) 8. 'Investigation of Things' ( gewu ) Chinese, in Neo-Confucian Philosophy, Xiao Ouyang (Wuhan University, China) 9. 'Casting Off the Bodymind ( shinjin-datsuraku )' in Japanese Philosophy, Rein Raud (Tallinn University, Estonia) 10. 'The Unconditioned' in Continental Philosophy, Russell Re Manning (Bath Spa University, UK) 11. 'Conventional Truth & Reality' in Indian and Greek Philosophy, Chiara Robbiano (Utrecht University, the Netherlands) 12. 'Epistemic Friction' in Jain Philosophy and Philosophy of Science, Anand Jayprakash Vaidya (San Jose State University, USA) 13. 'Foundations' in Daoist, Buddhist, and European Philosophy, Bryan William Van Norden (Yale-NUS College, Singapore) 14. Emptiness and 'Indigeneity in Buddhism, Jason Wirth (Seattle University, USA) 15. The Relegational Argument Form, Andrew K. Whitehead (Kennesaw State University, USA) Study Guide: Discussion Questions and Further Reading Part II: How We See Ourselves and Others Introduction, Sarah Flavel (Bath Spa University and International Academy for Chinese Thought and Culture , UK) and Chiara Robbiano (University College Utrecht, the Netherlands and Tohoku University, Japan) 16. 'Equity' in the Quran: Mosawah in Islamic Philosophy, Hadeer Aboelnagah (Prince Sultan University, Riyadh, Saudi Arabia) 17. 'Diversity' in Philosophy, Purushottama Bilimoria (University of Berkeley, California, USA) 18. 'I' as the Absolute Present in Japanese Philosophy, Yoko Arisaka (Hildesheim University, Germany) 19. 'Resonance' (gan ying) in Chinese Ethics, Rolf Elberfeld (University of Hildesheim, Germany) 20. 'Moral Responsiveness', in Buddhist Philosophy, Jay L. Garfield, ( Harvard Divinity School, USA) 21. 'Self-Directed Research' of Interested People (Tojisha-Kenkyu), in Japan and Neuroethics, Saku Hara (Tohoku University, Sendai, Japan) 22. 'Suffering' ( du?kha ) in Indian Philosophy, Stephen Harris (Leiden University, the Netherlands) 23. 'Karma' in Buddhist Philosophy, Peter Hershock (East-West Center, Honolulu, USA) 24. 'Double Movement', in the Continental European Philosophy, Evgenia Ilieva (Ithaca College, USA) 25. 'Self-Cultivation and Political Power in Feminism and Chinese Philosophy', Leah Kalmanson (Drake University, USA) 26. 'Relational Knowing, Caring and World Philosophies', Monika Kirloskar Steinbach (University of Konstanz, Germany) 27. 'Practice' For its Own Sake in Japanese Philosophy, John Maraldo (University of North Florida, USA) 28. "Ma" (In Between Spacetime) Henk Oosterling (Erasmus University Rotterdam, the Netherlands) 29. 'Action/Praxis' in Modern Korean Philosophy, Jin Y. Park (American University, USA) 30. 'I and Thou' in the Ecosophical Awareness, Michiko Yusa (Western Washington University, USA) Study Guide: Discussion Questions and Further Reading Part III: How We Express Ourselves Introduction, Sarah Flavel (Bath Spa University and International Academy for Chinese Thought and Culture , UK) and Chiara Robbiano (University College Utrecht, the Netherlands and Tohoku University, Japan) 31. ' Creativity', in 20th- Century European Philosophy (Bergson and Whitehead), Kiene Brillenburg Wurth (Utrecht University, the Netherlands) 32. 'Kata': Bodily Practice of Art as Intercultural Experience, Enrico Fongaro (Tohoku University, Japan) 33. 'Nature' in Indian Philosophy and Culture, Marzenna Jakubczak (Pedagogical University of Cracow, Poland) 34. Philosophy of 'Expression' in Modern Japanese Philosophy, Gereon Kopf (University of Iceland, Iceland) 35. 'Science Fiction' in/as Philosophy, Ethan Mills (University of Tennessee at Chattanooga, USA) 36. 'Mediation' in Japanese Philosophy of Technology, Kiyotaka Naoe (Tohoku University, Japan) 37. "Ritual" and Tradition in Confucian Education, Geir Sigur#sson (University of Iceland, Iceland) 38. Philosophy of Action in Japanese Philosophy, Mayuko Uehara (Kyoto University, Japan) 39. 'Concreteness' in Modern European Thought, Paul Ziche (Utrecht University, the Netherlands) Study Guide: Discussion Questions and Further Reading Conclusion Index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Asian philosophy; Islamic philosophy; Non-Western philosophy,Oriental & Indian philosophy,Islamic & Arabic philosophy; Electronic books